2018
DOI: 10.1016/j.ribaf.2017.07.130
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating capital flight through military expenditure: Insight from 37 African countries

Abstract: The purpose of this study is to assess the thresholds at which military expenditure modulates the effect of terrorism on capital flight. We employed a panel data of 37 African countries Depending on the terrorist target, the findings broadly show that a critical mass of between 4.224 and 7.363 of military expenditure as a percentage of GDP is needed to reverse the negative effect of terrorism on capital flight. In spite of the growing consensus of the need to utilise military expenditure to help combat terrori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 59 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The interaction term itself is significant. These results are quite consistent with the past studies (Asongu, 2016 and2017). Model 5 represents the result after introducing the interaction term of military expenditure with transnational terrorism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The interaction term itself is significant. These results are quite consistent with the past studies (Asongu, 2016 and2017). Model 5 represents the result after introducing the interaction term of military expenditure with transnational terrorism.…”
Section: Discussionsupporting
confidence: 91%
“…The fostering consequences of terrorism have an importance for both the academics and policymakers. (Efobi et al, 2016, Asongu et al 2017). Terrorism creates dissatisfaction in the community and reduce happiness and coordination in the community (Wouter and Piotr, 2018) The consequences of 9/11 terrorist attacks on stock markets, Madrid 2004 andin London 2005 have shown that terrorism is a new facet of risk that investors and financial institutions may be fronting (Marc Chesney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More insights into this position is available in Lai (2007) and Piazza (2008a). The stance has also been confirmed in a broad stream of terrorism literature (Schmid, 1992;Eubank & Weinberg, 1994;Drakos & Gofas, 2006;Piazza, 2007;Asongu & Amankwah-Amoah, 2018).…”
Section: Theoretical Underpinningsmentioning
confidence: 74%
“…The adopted elements in the conditioning information set are: internal conflicts, political globalisation, inflation, infrastructure, exchange rate and trade openness. The choice of these indicators in the conditioning information set is motivated by contemporary terrorism literature (Bandyopadhyay et al 2014, Efobi and Asongu 2016, Asongu and Biekpe 2018, Asongu and Amankwah-Amoah 2018. It is expected that trade openness, better infrastructure and improvements in exchange rate will have a positive incidence on the exports of resources (Akpan 2014, Asongu 2015a.…”
Section: Datamentioning
confidence: 99%